Structure–activity relationship of 18F-labeled PD-L1-targeting small molecule ligands: impact of radiolabeling strategy on affinity and in vivo performance - Fabian Krutzek; Cornelius K. Donat; Sven Stadlbauer (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Immune checkpoint inhibitor therapy addressing the PD-1/PD-L1 axis is a promising approach in cancer treatment. A clinically suitable radiotracer would allow molecular imaging of the temporospatial changes in tumor PD-L1 expression. This could enable the clinicians to select eligible patients for checkpoint therapy and monitor therapeutic efficacy. Results Four biphenyl-based small-molecule PD-L1 ligands were synthesized using a convergent synthetic route, with a linear sequence of up to eleven steps. Two candidates were covalently labeled with 18F via either an azido glycosyl or PEG2 moiety, while the other two were modified with a RESCA chelator for Al[18F]F2+-labeling. The lipophilicity was assessed through determination of log D 7.4 values. In vitro binding affinities (inhibition constant, K i) toward PD-L1 were determined in competition with one of our previously published biphenyl-based small-molecule (K D =  ~ 21 nM). Compared to this compound, both covalently labeled 18F-ligands exhibited decreased water solubility (log D 7.4 ~ − 2.5 and − 2.7), along with a markedly reduced (K i = 200‒500 nM) affinity. This was in line with in vivo small animal PET, where both compounds were characterized by a negligible tumor uptake, lack of contrast between target-positive/negative tumors and exclusively unfavorable hepatobiliary excretion. Similar results were observed for the chelator-modified ligands with slightly increased hydrophilicity (log D 7.4 ~ − 2.8 and − 2.9), showing a binding affinity of 150 nM for one compound, while binding was lost completely for the other. Again, a poor in vivo performance was observed, characterized by hepatobiliary clearance and lack of specific tumor uptake in the PD-L1 positive tumor. Conclusion Four biphenyl-based, 18F-labeled PD-L1 radioligands were developed using prosthetic groups (azido glycosyl or PEG2) for covalent fluorination and Al[18F]F2⁺-complexation with the RESCA chelator. Despite limited in vitro and in vivo performance, these fluorination approaches offer a foundation for developing improved PD-L1 radioligands after increasing the hydrophilicity and the spacing between the radiolabel and binding motif.